华北基性岩墙群的古地磁极及其哥伦比亚超大陆重建意义 - 侯贵廷; 黄宝玲; 杨默函; 王传成 (岩石学报, 2009)
从华北克拉通的中西部和东部发育的基性岩墙群获得三个精确定年的实际古地磁极位置(VGPs)。华北克拉通中西部恒山GU岩墙的斜锆石U-Pb年龄为1769±3Ma,该岩墙的古地磁给出古地磁极位置在北纬36°,东经247°(dp=2,dm=4);华北克拉通东部DY岩墙的斜锆石U-Pb年龄为1620.8±6.9Ma,获得的古地磁极位置为北纬6.9°东经81.9°(dp=4.31,dm=6.09);东部另一条岩墙LW4的SHRIMP U-Pb年龄为1157±18Ma,获得的古地磁极位置为北纬27.1°东经162°(dp=15.8,dm=18.7)。通过将这三个从基性岩墙获得的华北克拉通古地磁极位置与加拿大. One geomagnetic pole and two virtual geomagnetic poles (VGPs) are now available from U-Pb dated dyke swarms/individual dykes from the Eastern Block, Central Zone and Western Block of the North China craton. The precise baddeleyite U-Pb age of Hengshan GU dyke in the Central Zone is 1769 +/- 3Ma and is part of the Taihang dyke swarm. This swarm has yielded a paleomagnetic pole position at Plat = 36 degrees N, Plong = 247 degrees E(dp = 2 degrees, dm = 4 degrees). A dyke location DY in the Eastern Block of the North China craton yields a baddeleyite U-Pb age of a baddeleyite 1620.8 +/- 6.9Ma, and a VGP at Plat = 6.9 degrees N, Plong = 81.9 degrees E(dp = 4.31 degrees, dm = 6.09 degrees). A nearby dyke at site LW4 gives a zircon SHRIMP U-Pb age of 1157 +/- 18Ma and a VGP at Plat = 27.1 degrees N, Plong = 162 degrees E(dp = 15.8 degrees, dm = 18.7 degrees). Although secular variation has not been removed from the Shandong data, comparison of these three paleomagnetic pole positions of the North China craton with the Mesoproterozoic APWP of the Canadian Shield allows a continental reconstruction whereby the North China craton joined the supercontinent Columbia with the Canadian Shield from 1800 to 1600Ma, and the North China craton separated from the Canadian Shield sometime between 1600 to 1200Ma in response to final break-up of the supercontinent Columbia. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000264895900017&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 SCI(E) 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 8 03 650-658 25